(x-1)y" + 2y' = 0
If we expand about x=0, we assume
y = ∑anx^n
y' = ∑nanx^(n-1)
y" = ∑n(n-1)nx^(n-2)
Plug these into our DE and we have
(x-1)∑n(n-1)nx^(n-2) + 2∑nanx^(n-1) = 0
∑n(n-1)nx^(n-1) - ∑n(n-1)nx^(n-2) + 2∑nanx^(n-1) = 0
∑n(n-1)nx^(n-2) + ∑(2n+n-1)anx^(n-1) = 0
∑(n+1)(n+2)n+2x^n
+ ∑(3n+2)an+1x^n
∑((n+1)(n+2)n+2+(3n+2)an+1)x^n = 0
So, now we have the recurrence relation
(n+1)(n+2)n+2+(3n+2)an+1 = 0
I expect you can take it from here; if you get stuck, read the excellent article at
http://tutorial.math.lamar.edu/Classes/DE/SeriesSolutions.aspx
solve (x-1) (d^2 y)/〖dx〗^2 +2dy/dx=0 using series method
1 answer